Precursor in cotranslational secretion of diphtheria toxin. - Smith, W P (1980)
By extracellular labeling of peptides of intact Corynebacterium diphtheriae, followed by fractionation of the cells and chain completion by isolated polysomes, it is shown that diphtheria toxin is formed and secreted cotranslationally by membrane-bound polysomes; free polysomes from none. Moreover, when the chains on these polysomes were completed in vitro, in the absence of membrane they were found to include not only diphtheria toxin of a molecular weight of 62,000, but also a larger precursor of a molecular weight of 68,000. The precursor was identified by several properties: immune precipitation; conversion into toxin fragments A and B; adenosine diphosphate ribosyl-transferase activity after activation with trypsin; and cleavage to 62,000 daltons by membrane enzymes. The precursor yields an N-terminal A fragment with a broadened molecular weight distribution, compared with that from authentic toxin, thus supporting the expectation that the extra segment of the precursor is N-terminal.